Exil als Heterotopie. Die Dimensionen der Inneren Emigration und des Exils am Beispiel des literarischen Schaffens von Ernst Wiechert - Kardach, Magdalena (Studia Germanica Posnaniensia, 2017)
Ernst Wiechert (1887-1950) was an East Prussian-born author who remained mentally related to the natural and cultural landscape of that region. The relation was very strongly reflected in almost all his literary work. The article deals with defining what forms and spaces of emigration and inner emigration are specific to Wiechert. It positively verifies the present state of research which treats Wiechert as the representative of inner emigration. The article also indicates new spaces of emigration (heterotopia according to Michel Foucault's definition) and inner emigration of Wiechert by careful analysis of his autobiographical texts and literary work.